Social Networking Interaction In Foreign Language Teaching To Non-Linguistic Learners - Andreeva, Natalia; Ostroverkhaia, Irina (European Scientific Journal, ESJ, 2016)
This study investigates the practical experience of using social networking interaction for educational purposes. The feedback elicited from 82 members of the social networking “closed” “Flyingcats English” group was analyzed. The main findings reveal that social networking interaction allows to achieve certain teaching goals and meet learning needs of the digital generation of learners. Social networking interaction supplements the face-to-face classes and accumulates the best features of the Blended Learning technology such as round-the-clock and round-the-world availability and accessibility of training materials, ease of usage, enhancement of learning strategies and self-organization, increase of learners’ autonomy, eco-friendliness. The study highlighted that social networking interaction is able to perform informative, managerial, communicative, instructional, training, creative, productive, promotional, and inspirational functions. In summary, social networking interaction turns out to be a powerful motivational tool which encourages extrinsically motivated learners to become interested in improving skills and enhancing foreign language competence. The study found that an increase of the teacher’s time spent on electronic materials development and online activities represents a relative inconvenience of using social networks for educational purposes. Although, this inconvenience can be compensated by the fact that a great number of the teacher-made materials appear to be Reusable Learning Objects and can be used on a long term basis.